Mn(II),Fe(III),Co(II)and Rh(III) complexes with azo ligand: Synthesis, characterization, thermal analysis and bioactivity (Baghdad Science Journal, 2023)
New series of metal ions complexes have been prepared from the new ligand [4-Amino-N-(5-methyl-isaxazol-3-yl)-benzenesulfonamide] derived from Sulfamethoxazole and 3-aminophenol. Accordingly, mono-nuclear Mn(II), Fe(III), Co (II), and Rh(III) complexes were prepared by the reaction of previous ligand with MnCl2.4H2O, CoCl2.6H2O, FeCl3.6H2O and RhCl3H2O, respectively. The compounds have been characterized by Fourier-transform infrared (FTIR), ultraviolet–visible (UV–vis), mass, 1H-, and 13C-nuclear magnetic resonance (NMR) spectra and thermo gravimetric analysis (TGA& DSC) curve, Bohr magnetic (B.M.), elemental microanalyses, metal ions, chloride containing, and molar conductance.These reviews uncovered octahedral geometries for complexes. The investigation of complexes development by means at molar proportion andoccupation strategy in DMF solution has been researched, and results were reliable to those found in the solid complexes with a proportion of (M:L) as (1:2).